Dietary trends among Polish women in 2011–2022—cross-sectional study of food consumption frequency among women aged 20–50 in Silesia region, Poland - Białek-Dratwa, Agnieszka; Kokot, Teresa; Czech, Elżbieta; Całyniuk, Beata; Kiciak, Agata; Staśkiewicz, Wiktoria; Stanjek-Cichoracka, Anita; Słoma-Krześlak, Małgorzata; Sobek, Olga; Kujawińska, Maria; Grot, Martina; Szczepańska, Elżbieta; et al. (Frontiers in Nutrition, 2023)
Background: Women's nutrition should be different from that of men. Women have lower energy requirements than men. And the need for certain vitamins and minerals is higher in women, this applies to iron, calcium, magnesium, vitamin D and vitamin B9 (folic acid). This is related to hormonal changes including menstruation, pregnancy, breastfeeding and the onset of menopause. Through hormonal changes and the changing physiological state, women are at greater risk of anaemia, bone weakness and osteoporosis. The aim of the study was to assess changes in the dietary pattern among women from the Silesian Agglomeration in Poland between 2011 and 2022. Material and method: The survey was conducted in 2011 (March-May 2011) and in 2022 (October-November 2022) among women living in the Silesian Agglomeration (Silesia Region) in Poland aged 20-50. After consideration of the inclusion and exclusion criteria, 745 women were included in the final analysis, including 437 women screened in 2011 and 308 women screened in 2022. The research tool used in this publication was a survey questionnaire consisting of 2 parts. The first part of the questionnaire consisted of demographic data. The second part of the study focused on the dietary habits of the women surveyed and the frequency of consumption of individual foods (FFQ). Results: Women in 2022 were more likely to consume fast-food (p=0.001), salty snacks (chips, crisps) (p<0.001) and sweets (p<0.001). Women in 2022 were more likely to consume whole-grain bread (p<0.001), wholemeal pasta (p<0.001), brown rice (p<0.001), oatmeal (p<0.001), buckwheat groats (p=0.06), and bran (p<0.001) than women in 2011. Women in 2022 were significantly more likely to consume vegetables (p<0.001) than women in 2011. Conclusions: Based on the study, we can draw the following conclusions: there have been changes in the diet of women living in Silesia (Poland) over the last decade. The results of the study will help determine the future direction of nutrition education, taking into account current dietary mistakes, in order to minimise the negative impact of nutrition on women's future health and to formulate ministerial prevention programmes.